The Nature and Severity of Adverse Events in Select Outpatient Surgical Procedures in the Veterans Health Administration. Issue 3 (July 2018) - Mull, Hillary J.; Itani, Kamal M. F.; Charns, Martin P.; Pizer, Steven D.; Rivard, Peter E.; Hawn, Mary T.; Rosen, Amy K.
Abstract : Background: Research on adverse events (AEs) in outpatient surgery has been limited. As part of a Veterans Health Administration (VA) project on AE surveillance, we chart-reviewed selected outpatient surgical cases to characterize the nature and severity of AEs. Methods: We abstracted financial year 2012-2015 VA outpatient surgery cases selected with high (n = 1185) and low (n = 1072) likelihood of an AE based on postoperative health care utilization. The abstraction tool included established AE definitions and validated harm and severity scales. Results: We found AEs in 608 high-likelihood (51%) and 126 low-likelihood outpatient surgical procedures (12%). Among 1010 unique AEs, the most common were wound issues (n = 261, 26%), urinary retention (23%), and urinary tract infections (12%). While 63% of all AEs involved minimal harm, 28% required hospitalization, and 9% were severely harmful including 8 AEs requiring intervention to sustain life and 2 deaths. Overall, 102 AEs (10%) required, at minimum, a repeat surgery to treat. Conclusions: Among VA outpatient surgical procedures selected based on likelihood of an AE, nearly 40% of identified events carried more than minimal patient harm, undermining the claim that outpatient surgery is relatively safe. Prevalent and preventable AEs such as wound dehiscence and urinary retention may be useful targets for quality improvement. Abstract : Supplemental Digital Content is Available in the Text.